Axonal degeneration in Alzheimer’s disease: When signaling abnormalities meet the axonal transport system - Kanaan, Nicholas M. (2012)
Alzheimer’s disease (AD) is characterized by progressive, age-dependent degeneration of neurons in the central nervous system. A large body of evidence indicates that neurons affected in AD follow a dying-back pattern of degeneration, where abnormalities in synaptic function and axonal connectivity long precede somatic cell death. Mechanisms underlying dying-back degeneration of neurons in AD remain elusive but several have been proposed, including deficits in fast axonal transport (FAT). Accordingly, genetic evidence linked alterations in FAT to dying-back degeneration of neurons, and FAT defects have been widely documented in various AD models. In light of these findings, we discuss experimental evidence linking several AD-related pathogenic polypeptides to aberrant activation of signaling pathways involved in the phosphoregulation of microtubule-based motor proteins. While each pathway appears to affect FAT in a unique manner, in the context of AD, many of these pathways might work synergistically to compromise the delivery of molecular components critical for the maintenance and function of synapses and axons. Therapeutic approaches aimed at preventing FAT deficits by normalizing the activity of specific protein kinases may help prevent degeneration of vulnerable neurons in AD.